1996
DOI: 10.1159/000154324
|View full text |Cite
|
Sign up to set email alerts
|

p53 Polymorphisms and Haplotypes Show Distinct Differences between Major Ethnic Groups

Abstract: Three different p53 DNA polymorphisms (a 16-bp duplication in intron 3 and BstUland MsplRFLPs in exon 4 and intron 6, respectively) and haplotype combinations were studied in some major ethnic groups: Caucasians (Swedes), Chinese, Dravidian Indians and African Blacks. Significant ethnic differences in single polymorphisms were found between all groups except for African Blacks-Dravidian Indians, who differed only in their MspI7-16-bp duplication haplotype distribution. Since previous results have shown that p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 19 publications
5
53
0
2
Order By: Relevance
“…The haplotypes constructed have been expressed in the order intron 3-codon 72-intron 6. 24 In our study, 6 of 8 possible haplotypes were observed in all groups. The haplotype frequencies were significantly different between leukoplakia and controls (p 5 0.008; Table VI).…”
Section: Resultssupporting
confidence: 51%
See 4 more Smart Citations
“…The haplotypes constructed have been expressed in the order intron 3-codon 72-intron 6. 24 In our study, 6 of 8 possible haplotypes were observed in all groups. The haplotype frequencies were significantly different between leukoplakia and controls (p 5 0.008; Table VI).…”
Section: Resultssupporting
confidence: 51%
“…28,32,34,43 Similar analysis with third generation Dravidian Indians from Singapore reported the codon 72 allele 1 frequency as 0.54. 24 In this study, allele 1 frequency in controls was found to be 0.52. The frequency of allele 1 (intron 6 uncut variant) at the NciI locus (nt 13494) has been reported as 0.02 in the Chinese, 0.19 in south Indians and African blacks, 0.22 in Hispanic population and 0.33 in African Americans.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations